Pengaruh Gaya Hidup, Konsep Diri, Harga Dan Kelas Sosial Terhadap Pengambilan Keputusan Pembelian Konsumen Di Coffeshop Kedai Kopi Pacar Hitam Lampung - Wuryanti, Lestari; Zahara, Yeni (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2019)
The purpose of this study is to know how big the influence of life style, self concept, price,social class toward decision making of purchase by consumer at coffeeshope kedai kopi pacar hitamlampung.Research methods in this study are observation, and questioner by using likert scale and samplingmethods that being used are nonprobability sampling and purpossive sampling as many as 100samples is multiple linear regression method.From four variables in this study shows that variable that influence decision making of purchase byconsumer is price which being proved by significancy < 0,05 meanwhile variables that has no impacttoward decision making of purchase by consumer is life style, self concept, and social class withsignificancy > 0,05, furthermore F test shows all variables silmutaneously have significant impacttoward decision making of purchase by consumer with significancy 0,000.Keywords : Life style, self concept, price, social class and decision making of purchase by consumer